Protection strategies of active defense in cyber-physical power systems. (1st November 2021) - Chen, Lei; Gorbachev, Sergey; Yue, Dong; Dou, Chunxia; Li, Shengquan; Ge, Hui; Cheng, Zihao
Abstract: Cascading failure triggered by tiny failure iteratively propagates between physical power grid and communication network, causing severe damage on cyber-physical power systems. In this paper, we study the protection strategies of active defense to improve the robustness of systems. Based on analysis of cascading failure in systems, we classify failure into three types, structural failure, overload failure, and interdependent failure. Due to the severe damage caused by overload failure, we propose four protection strategies of active defense, through interdicting propagation path of cascading failure, to prevent overload failure. Compared with traditional redundancy protection and structure optimization, the protection strategies are economical and efficient, and can defend from an unknown attack. In simulation analysis, the protection strategies of active defense are proved to be effective in prevention of cascading failure.